Fluent forever (revised edition) ebook How to learn any language fast and never forget it. - Wyner, Gabriel (2014)
The bestselling guide to learning a new language and remembering what you learned, now revised and updated “A brilliant and thoroughly modern guide . . . If you want a new language to stick, start here.”—Gary Marcus, cognitive psychologist and author of the New York Times bestseller Guitar Zero Gabriel Wyner speaks seven foreign languages fluently. He didn’t learn them in school—who does? Rather, he mastered each one on his own, drawing on free online resources, short practice sessions, and his knowledge of neuroscience and linguistics. In Fluent Forever, Wyner shares his foolproof method for learning any language. It starts by hacking the way your brain naturally encodes information. You’ll discover how to hear new sounds and train your tongue to produce them accurately. You’ll connect spellings and sounds to images so that you start thinking in a new language without translating. With spaced-repetition systems, you’ll build a foundation for your language in a week and learn hundreds of words a month—with just a few minutes of practice each day. This revised edition also shares fresh strategies that Wyner has refined over years of study. You’ll learn to • use your interests to curate vocabulary that you’ll actually be excited to study • fast-track fluency, with a new appendix devoted to conversation strategies with native speakers • compile the best language-learning tool kit for your budget • harness the science of motivation and habit building to turbocharge your progress • find the perfect level of difficulty with reading and listening comprehension to stay engaged and avoid frustration With suggestions for helpful study aids and a wealth of free resources, the intuitive techniques in this book will offer you the most efficient and rewarding way to learn a new language.